O35 The impact of COVID-19 on access and availability of radiological imaging and surgical intervention at the east Midlands major trauma centre: an icon trauma study. (30th July 2021) - Seehra, J K; Lewis-Lloyd, C; Gida, G; Adiamah, A; Brooks, A
Abstract: Introduction: During the COVID‐19 pandemic, Major Trauma services were subject to significant challenges including reduced access to Computed Tomography (CT) scanning and restrictions on operative intervention due to limited intensive care beds. This study evaluated the pandemic's impact on access and timeliness of imaging and surgical intervention. Method: This observational study compared 2 cohorts of patients admitted in a 10-week period during the COVID-19 pandemic and a similar time period in 2019. Variables included demographics, time to CT scan and to surgery and operative characteristics. Statistical comparisons were undertaken using Mann Whitney U, Fisher's exact and Chi-squared tests. Result: Of 642 patients, 405 were admitted in 2019 and 237 in 2020 representing a 41.5% absolute reduction in trauma admissions during the pandemic. There were no statistical differences ( P = 0.2585) between arrival to the Emergency Department and time to CT scan across both years (median 42 minutes) or between operative approach ( P = 0.728) and level of post-operative care ( P = 0.788). However, there were statistical differences in time to surgery ( P = 0.0193) and operative length ( P = 0.0141) with a 2-fold increase in overnight operating, 31.2% increase in patients operated on < 24 hours from admission, and 42.9% reduction in surgery lasting >120 minutes during the COVID-19 pandemic. Conclusion: Early robust restructuring of trauma services during the COVID-19 pandemic ensured timely access to appropriate imaging and surgery for major trauma injured patients. The higher rates of overnight surgery and shorter duration of procedure were likely explained by the increased onsite availability of suitably trained trauma surgical teams. Take-home Message: COVID-19 had the potential to significantly impact Major Trauma services, however excellence in patient care was maintained by quick restructuring to staff, space and services Improvements to the Major Trauma pathway have become ingrained into daily practice and optimised for future outbreaks.